Dissociated perceptual-sensory and exploratory-motor neglect. - Liu, G T (1992)
A patient with a right sided parietal lobe infarction manifested left sided sensory extinction in the visual, auditory, and tactile modalities but had only mild exploratory-motor neglect. In contrast, another patient with a right frontal haemorrhage demonstrated only left sided exploratory-motor hemispatial neglect. Tasks that combined perceptual and exploratory features elicited varying degrees of neglect in each patient. These two cases with dissociated neglect behaviour lend further evidence for behavioural specialisation within components of a cortical network for directed attention: sensory-representational aspects mediated primarily by the parietal component, motor-exploratory primarily by the frontal component. These cases also highlight the need to include and distinguish among several different measures of neglect in the clinical investigation of patients with hemispatial inattention.